1989
DOI: 10.1084/jem.169.4.1435
|View full text |Cite
|
Sign up to set email alerts
|

Antiglomerular basement membrane nephritis in beige mice. Deficiency of leukocytic neutral proteinases prevents the induction of albuminuria in the heterologous phase.

Abstract: Antiglomerular basement membrane (GBM) nephritis with massive albuminuria can be induced in mice by injection of heterologous antibodies against mouse GBM. The albuminuria and the glomerular lesions in this model are not mediated by complement, but are dependent on the presence of polymorphonuclear granulocytes (PMN) in the glomeruli. Neutral serine proteinases and reactive oxygen metabolites produced by activated PMN have been implicated as agents contributing to tissue damage. We examined the role of leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 33 publications
5
37
0
Order By: Relevance
“…It is possible that the dose of anti-rat rMMP-12 Ab was not enough, and MMP-12-deficient mice, which lack production of MMP-12 genetically (14), should be used to elucidate the role of MMP-12 more clearly in further study. However, given that glomerular injury is also induced by several proteinases, such as serine proteinase, elastase, and cathepsin G, or reactive oxygen metabolites from neutrophils (37)(38)(39), reactive oxygen species from macrophages (40), or also induced by direct killer activity of CD8 ϩ cells (32), our results on the effect of MMP-12 neutralization may be compatible with the fact that MMP-12 is one of the major factors, but not the absolute factor, of glomerular injury. In the present study, some of these other important mediators of glomerular injury were not detected by the gene expression profiling analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the dose of anti-rat rMMP-12 Ab was not enough, and MMP-12-deficient mice, which lack production of MMP-12 genetically (14), should be used to elucidate the role of MMP-12 more clearly in further study. However, given that glomerular injury is also induced by several proteinases, such as serine proteinase, elastase, and cathepsin G, or reactive oxygen metabolites from neutrophils (37)(38)(39), reactive oxygen species from macrophages (40), or also induced by direct killer activity of CD8 ϩ cells (32), our results on the effect of MMP-12 neutralization may be compatible with the fact that MMP-12 is one of the major factors, but not the absolute factor, of glomerular injury. In the present study, some of these other important mediators of glomerular injury were not detected by the gene expression profiling analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulfate constitutes the majority of anionic sites of the capillary permeability barrier and also contributes to the anticoagulant properties of GBM exposed through the glomerular endothelium fenestrae. Experiments performed in Beige mice, which have a congenital defect in neutrophil granules, have demonstrated the involvement of neutrophil proteinases in the induction of albuminuria in the heterologous phase of anti-GBM nephritis (Schrijver et al, 1989). While the importance of neutrophils in mediating glomerular injury has been well demonstrated in this experimental model, the pathogenetic role of these cells in human immune complex mediated glomerunephritis remains to be elucidated.…”
Section: Iie Immune Complex-induced Inflammation: Antibody-mediatedmentioning
confidence: 99%
“…PMN are thought to damage glomeruli, including in this disease, due to a combination of reactive oxygen species and proteolytic enzymes (7). Previous studies with this model in cathepsin G/elastase deficient-mice (23,24) and an injection of a cysteine proteinase inhibitor (25) demonstrated that only early proteinuria (within day 1) was dependent on proteinase, but PMN influx and development of glomerular injury were not. Thus, we postulated that the FcR-mediated PMN respiratory burst may be a rapid and powerful effector mechanism in the early cell recruitment.…”
Section: Mmune Complex (Ic)mentioning
confidence: 99%